Description of the larva of Tetragonoderus (Crossonychus) variegatus Dejean, 1829 (Coleoptera: Carabidae: Cyclosomini) with notes on biology - Santos, Guilherme Ide Marques Dos (Zootaxa, 2015)
A late instar of the Tetragonoderus (Crossonychus) variegatus Dejean, 1829 larva is described for the first time, and is compared with its first instar, with the larva of another Tetragonoderus species, and with the larva of one Cyclicus species. Habitus and important structures of the larva are illustrated, as well the adult’s membranous wings. Some aspects of the natural history of the larva and adult are also noted.